(untitled) (Journal of Pathology of Nepal, 2018)
Medical malpractice is defined as any act or omission by a physician during treatment of a atient that deviates from accepted norms of practice in the medical community and causes an injury to the patient. In the United States, Medical malpractice is a specific subset of tort law that deals with professional negligence. “Tort” is the Norman word for “wrong,” and tort law is a body of law that creates and provides remedies for civil wrongs that are distinct from ontractual duties or criminal wrongs.Although the laws of medical malpractice differ significantly between nations, as a broad general rule liability follows when a health care practitioner does not show a fair, reasonable and competent degree of skill when providing medical care to a patient.